Proteomic Characterization of Pig Sperm Anterior Head Plasma Membrane Reveals Roles of Acrosomal Proteins in ZP3 Binding. Issue 2 (February 2015) - Kongmanas, Kessiri; Kruevaisayawan, Hathairat; Saewu, Arpornrad; Sugeng, Clarissa; Fernandes, Jason; Souda, Puneet; Angel, Jonathan B.; Faull, Kym F.; Aitken, R. John; Whitelegge, Julian; Hardy, Daniel; Berger, Trish; et al.
<x xml:space="preserve">Abstract</x> The sperm anterior head plasma membrane (APM) is the site where sperm first bind to the zona pellucida (ZP). This binding reaches the maximum following the sperm capacitation process. To gain a better understanding of the sperm‐ZP binding mechanisms, we compared protein profiles obtained from mass spectrometry of APM vesicles isolated from non‐capacitated and capacitated sperm. The results revealed that ZP‐binding proteins were the most abundant group of proteins, with a number of them showing increased levels in capacitated sperm. Blue native gel electrophoresis and far‐western blotting revealed presence of high molecular weight (HMW) protein complexes in APM vesicles of both non‐capacitated and capacitated sperm, but the complexes (∼750–1300 kDa) from capacitated sperm possessed much higher binding capacity to pig ZP3 glycoprotein. Proteomic analyses indicated that a number of proteins known for their acrosome localization, including zonadhesin, proacrosin/acrosin and ACRBP, were components of capacitated APM HMW complexes, with zonadhesin being the most enriched protein. Our immunofluorescence results further demonstrated that a fraction of these acrosomal proteins was transported to the surface of live acrosome‐intact sperm during capacitation. Co‐immunoprecipitation indicated that zonadhesin, proacrosin/acrosin and ACRBP interacted with each other and they may traffic as a complex from the acrosome to the sperm surface. Finally, the significance of zonadhesin in the binding of APM HMW complexes to pig ZP3 was demonstrated; the binding ability was decreased following treatment of the complexes with anti‐zonadhesin antibody. Our results suggested that acrosomal proteins, especially zonadhesin, played roles in the initial sperm‐ZP binding during capacitation. J. Cell. Physiol. 230: 449–463, 2015. © 2014 Wiley Periodicals, Inc.